Dietary Inflammatory Index Is Related to Heart Failure Risk and Cardiac Function: A Case–Control Study in Heart Failure Patients - Moludi, Jalal; Shivappa, Nitin; Alisgharzadeh, Soghra; Hébert, James R.; Alizadeh, Mohammad (Frontiers in Nutrition, 2021)
Aims: Previous studies suggest that diet and inflammation are important risk factors for heart failure (HF); however, the associations remain unclear. The Dietary Inflammatory Index (DII®) was established to measure the inflammatory capacity of individuals' diet. This study aimed to explore the DII in HF subjects compared with controls. Methods and Results: We conducted a case–control (116 cases and 113 controls) study that recruited in the similar clinics. DII scores were calculated based on dietary intakes. N-Terminal pro-brain natriuretic peptide (NT-proBNP) levels and ejection fraction (EF) were assessed in both groups. In order to analyze DII scores with HF as the outcome, we used conditional logistic regression. A linear regression was applied to explore the associations between the DII and left ventricular EF (LVEF). There was statistically significant difference in DII scores in cases vs. controls (−0.16 ± 1.37 vs. −0.33 ± 1.67; p = 0.040). Conditional logistic regression has shown that subjects with higher DII scores had higher risk of HF. For every one-point rise in DII score, the odds of having HF increased by 30% (OR: 1.30; CI: 1.03, 1.69; p = 0.047). The EF was inversely associated with saturated fatty acid (β = −0.34, 95% CI: −0.61, −0.07; p = 0.012). Subjects with higher DII scores had higher NT-proBNP levels and had lower EF. Conclusion: The DII score was associated with high probability of HF. It appears that consumption of anti-inflammatory diet may lead to the prevention of HF and therefore suggests that dietary modification with the goal of reducing DII scores could be a valuable strategy for improving clinical outcomes in these patients.